Epidemiological Study on the Colonization of Chickens with Campylobacter in Broiler Farms in Malaysia : Possible Risk and Management Factors - A.A., Saleha (International Journal of Poultry Science, 2004)
Nineteen chicken flocks from ten broiler farms were studied for the colonization of Campylobacter. A variety of factors such as farm location and chicken house structure, water source, rearing practice and hygiene management were investigated. Each flock was sampled weekly, from day-old-chicks to slaughter-age chickens and environmental samples which include water, feed, wood shavings, flies and chicken house environment were collected to examine for the presence of Campylobacter. In all farms, Campylobacter was not detected in one- and seven-day-old chicks. Campylobacter was first detected in 38.2% of 14-day-old-chicks and 45.3% of 21-day-old chickens. Samples of feed, wood shavings, flies and chicken house environment were all negative while only 1.5% of untreated water supplies were found positive for campylobacters. Prevalence of campylobacters` colonization was possibly associated with untreated water, presence of other animals and unhygienic management practices; also flying birds could be a source as they were found to harbour campylobacters; in one farm where `fishing net` was placed over the chicken house to prevent birds from entering, Campylobacter was not isolated in the chickens up to slaughter age.